Do more mature preterm babies with surgical necrotizing enterocolitis predominantly develop the colonic disease? - Sarah Martin; Chandrasen K Sinha; Iona Ashworth; Sadaf Bhayat; Anay Kulkarni (BMJ Publishing Group, 2021)
Background The primary aim was to scrutinize our hypothesis: "Do more mature preterm (MMP) babies with surgical necrotizing enterocolitis (NEC) predominantly develop the colonic disease and are different in their response and behaviour in comparison to exceedingly preterm (EP) babies?" Secondary outcomes were to define time taken in developing NEC, time from diagnosis to laparotomy, requirement of parenteral nutrition (PN), and ventilatory support.Methods We defined MMP babies as ≥30 weeks of gestation and EP babies as ≤29 weeks+6 days of gestation. Inclusion criteria were all babies <37 weeks with NEC requiring surgery (called surgical NEC group). Data were collected retrospectively and analyzed using QuickCalcs.Results Of the total, 41% (97/234) of babies underwent laparotomy between 2010 and 2019. Totally, 81% were EP and 19% were MMP babies. Pure colonic involvement was seen in 9% of EP babies in comparison to 56% in the MMP babies (p=0.0001). Involvement of only the small bowel was seen in two-thirds of EP babies in comparison to only one-third in MMP babies (p=0.01). EP cohort required PN for 82 days (median) in comparison to 17 days (median) in the MMP cohort (p=0.001). Ventilation requirement in the EP group versus the MMP group was 24 vs 9 days (median), respectively (p=0.0006).Conclusions MMP babies predominantly developed colonic disease, whereas EP babies predominantly developed small bowel disease. EP babies required a longer duration of PN and ventilation support. This study opens a new area of research to differentiate pathogenesis and maturation patterns of the small and large bowels in babies with NEC.